Information Value And Investor Wealth - The Case Of Earnings Announcements - Cready, Wm (Journal of Accounting Research, 1988)
This paper empirically investigates the relation between investor wealth and the value of annual and quarterly earnings announcements as implied by (1) the behavior of mean stock trade transaction sizes at announcement dates, and (2) transaction size-stratified trading activity in postannouncement time periods. Announcement-period mean transaction sizes are found to exceed expected mean transactions sizes estimated from trading activity occurring in nonannouncement periods. This result is attributed to a greater relative trading response to earnings announcements by wealthier investors, consistent with Ohlson's [1975] proposition that information value increases with investor wealth in a security market setting. Further evidence of a positive relation between value and wealth is found when postearnings announcement stock transactions are stratified by share size into three strata, where the first stratum (small stratum) is transactions of 100 and 200 shares, the second stratum (large stratum) is transactions of 300 to 900 shares, and the third stratum (institutional